Pharmacotherapy in Bronchopulmonary Dysplasia: What Is the Evidence? - Sakaria, Rishika P.; Dhanireddy, Ramasubbareddy (Frontiers in Pediatrics, 2022)
Bronchopulmonary Dysplasia (BPD) is a multifactorial disease affecting over 35% of extremely preterm infants born each year. Despite the advances made in understanding the pathogenesis of this disease over the last five decades, BPD remains one of the major causes of morbidity and mortality in this population, and the incidence of the disease increases with decreasing gestational age. As inflammation is one of the key drivers in the pathogenesis, it has been targeted by majority of pharmacological and non-pharmacological methods to prevent BPD. Most extremely premature infants receive a myriad of medications during their stay in the neonatal intensive care unit in an effort to prevent or manage BPD, with corticosteroids, caffeine, and diuretics being the most commonly used medications. However, there is no consensus regarding their use and benefits in this population. This review summarizes the available literature regarding these medications and aims to provide neonatologists and neonatal providers with evidence-based recommendations.